KONTRIBUSI KOLAM IKAN "YUMINA BUMINA" SEBAGAI UPAYA PENINGKATAN PENDAPATAN KELUARGA DIDESA JAMPANG BOGOR - Rakhmawati Oktavianna; Aditya Pratama; sulistiyani sulistiyani (Economy Deposit Journal (E-DJ), 2019)
Jampang Village is one of the villages in the Kemang sub-district area and is included in the Bogor district. Jampang Village has been named the biggest fish producing village in Bogor Regency. Fish cultivation is the biggest source of livelihood for the residents of Jampang Village. The number of people as freshwater fish aquaculture practitioners is able to produce several innovations in the use of ponds that are named YUMINA ponds (vegetables and fish). Yumina Bumina Pond is a pond that not only produces freshwater fish but is also able to produce certain vegetables and fruits by utilizing freshwater fish farming. The formulation of the problem in this study are: How is the contribution of the fish pond "Yumina Bumina" as an effort to increase family income in the Village Jampang Bogor؟. The purpose of this study was to analyze the contribution of the fish pond "Yumina Bumina" as an effort to increase family income in the village of Jampang, Bogor. Data analysis methods in this study have several stages that must be met. The first stage is the stage of observation - this stage is the stage of data collection using observation techniques - interview and documentation techniques. The second stage is the stage of redu redu data ، with this stage as the process of selection and focusing of existing data in the field. The third step is the data presentation stage - this stage compiles all the information that has been collected. The fourth stage is the stage of drawing conclusions - this stage is the last stage of data analysis. The location of this research is in the village of Jampang ، Bogor and the sample of this study is the sluice fish farmers in the village of Jampang ، Bogor